EP1079 Clearance of HPV in women received conization related with mycoplasma and Ureaplasma. (1st November 2019) - Kim, CJ; Lee, SJ; Lee, KH; Lee, YS; Park, JS; Park, TC
Abstract : Introduction/Background: Little is known about risk factors for persistent high-risk infection after cervical conization. We compared the duration of high risk HPV among women with cervical conization by exposure to sexually transmitted infections(STIs) using a real time PCR methods. Methodology: This study was conducted on 28 patients who received conization due to persistent CIN-1, CIN-2, 3 and CIS at the St Paul's Hospital of the Catholic University of Korea from Jul, 2014 until Feb, 2018. They all were positive for high risk HPV at initial visit. A specimens were tested using realtime based assay, Anyplex II STI-7 (Seegene, Korea). tients were followed in 4–6 month interval with Pap smear and Anyplex TM Real time PCR HPV 28 detection method which detect 19 high-risk HPV genotype, 9 low-risk genotypes Results: The mean age was 39.3 years (Min-Max : 26–50) and mean follow-up month was 20.2 month(Min-Max :3–41 month). ASCUS, LSIL, ASCH and HSIL were 8, 6, 3 and 11 women. Single and multiple HPV detection was 14 and 14 (50%). Of the women received conization, median clearance time of those multiple type HPV was 26 month and that was slightly longer than single type HPV(24.5 month, P>0.05). Mycoplasma, Chlamydia and Ureaplasma positive cases were 10(35.7%), 1(3.6%) and 18(64.3%).The median clearance of women infected with Mycoplasma and Ureaplasma were 22.4 and 29.8 months. Ureaplasma positive women had longer clearance time compared with negative women(29.8 month vs 24.8 month p>0.05). HPV types were related with clearance time. Mean clearance of alpha-9 group HPV(HPV-16, 31, 33, 35, 52, 58) was shorter than alpha-7(HPV-18, 39, 45, 59, 68, 70) and alpha-6(HPV-53, 56, 66). (20.9 month vs 28.8 month p<0.05). Conclusion: In a follow-up after conization, women with Ureaplasma showed relatively long time persistence. Management of this STI could reduces risk for high risk HPV persistence. Disclosure: Nothing to disclose